GUIDELINES FOR LINGUISTICS STUDENTS' INDEPENDENT WORK: IMPLEMENTING TBLT PRINCIPLES IN ASSIGNMENT COMPLETION - Djurakulova Diyora Alisher qizi (American Journals Publishing, 2024)
This research outlines the application of TBLT principles in independent linguistic tasks, emphasizing the importance of vocabulary development and purposeful activities. Drawing inspiration from communicative language education, the vocabulary activity adheres to Jane Willis's guidelines, guaranteeing student involvement and connections to real-life scenarios. Collaboration and discussion are encouraged through pair work in the Category Classification task, aligning with the principles of communicative language instruction.
Keywords: TBLT principles, linguistics students, independent tasks, vocabulary development, communicative language education, Jane Willis's criteria, student engagement, real-world connections, category classification task.